Penicillin-binding protein encoded by pbp4 is involved in mediating copper stress in Listeria monocytogenes. Issue 20 (4th October 2017) - Parsons, Cameron; Costolo, Ben; Brown, Phillip; Kathariou, Sophia
Abstract: Listeria monocytogenes raises major food safety and public health concerns due to its potential for severe foodborne disease and persistent colonization of food processing facilities. Copper is often employed to control pathogens in agriculture and is increasingly used in healthcare facilities, but mechanisms mediating tolerance of L. monocytogenes to copper remain poorly understood. A mariner- based mutant library of L. monocytogenes 2011L-2858, implicated in the 2011 listeriosis outbreak via whole cantaloupe, was screened for growth at sublethal levels of copper yielding mutant G2B4 with decreased copper tolerance. The transposon was localized in pbp4 ( lmo2229 homolog), encoding a penicillin-binding protein (PBP) . In addition to reduced copper tolerance, G2B4 exhibited increased susceptibility to β-lactam antibiotics, reduced biofilm formation and reduced virulence in the Galleria mellonella model. Mutant phenotypes were fully restored upon genetic complementation of G2B4 with intact pbp4 . Findings provide the first evidence for the role of a PBP in copper tolerance of L. monocytogenes and suggest that pbp4 may be a suitable target to enable the use of lower levels of copper or enhance the effectiveness of levels currently in use. Given the wide distribution of PBPs and their highly conserved nature, this could have profound impacts in regard to ecology and control of L. monocytogenes and other microorganisms. Abstract : Inactivation of L. monocytogenes penicillin-binding protein decreases copper tolerance, β-lactam tolerance, biofilm formation and virulence potential, indicating its suitability as a drug target and future management strategies for L. monocytogenes .